Pengaruh Strategi Penetapan Harga, Promosi dan Kualitas Produk Terhadap Kepuasan Konsumen Fashion Di toko SCH Kota Malang - Septiani, Ananda Natasya; Hidayati, Nur; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze whether there is an effect of pricing strategies, promotions and product quality on customer satisfaction. The population in the study of consumers who have bought or used Fashion SCH products in Malang City, the sample collected was 80 respondents. The sampling technique used purposive sampling. This study uses primary data. The data analysis method uses multiple linear regression analysis tests. The findings of this study are that pricing strategy has a significant effect on customer satisfaction, promotion has a significant effect on customer satisfaction and product quality has a significant effect on customer satisfaction. Keywords: Pricing Strategy, Promotion, Product Quality, Consumer Satisfaction